Genomic variations in plasma cell free DNA differentiate early stage lung cancers from normal controls. Issue 1 (October 2015) - Xia, Shu; Huang, Chiang-Ching; Le, Min; Dittmar, Rachel; Du, Meijun; Yuan, Tiezheng; Guo, Yongchen; Wang, Yuan; Wang, Xuexia; Tsai, Susan; Suster, Saul; Mackinnon, Alexander C.; et al.
Highlights: Developed a novel plasma genomic abnormality (PGA) score for CNV analysis. Demonstrated potential use of PGA scores in early detection of lung cancer. Showed detectable gene mutations in early stage lung cancer. Abstract: Objectives: Cell free tumor DNA (cfDNA) circulating in blood has a great potential as biomarker for cancer clinical management. The objective of this study is to evaluate if cfDNA in blood plasma is detectable in early stage lung cancer patients. Materials and methods: We extracted cfDNAs and tumor tissue DNAs from 8 lung adenocarcinoma patients. We also extracted cfDNAs from 8 normal controls. To evaluate copy number variations (CNV) and identify potential mutations, we performed low pass whole genome sequencing and targeted sequencing of 50 cancer genes. To accurately reflect the tumor-associated genomic abnormality burden in plasma, we developed a new scoring algorithm, plasma genomic abnormality (PGA) score, by summarizing absolute log2 ratios in most variable genomic regions. We performed digital PCR and allele-specific PCR to validate mutations detected by targeted sequencing. Results and conclusions: The median yield of cfDNA in 400ul plasma was 4.9ng (range 2.25–26.98 ng) in patients and 2.32 ng (range 1.30–2.81 ng) in controls ( p = 0.003). The whole genome sequencing generated approximately 20 million mappable sequence reads per subject and 5303 read counts per 1 Mb genomic region. Log2 ratio-based CNV analysis showed significant chromosomal abnormality in cancer tissue DNAs and subtle but detectable differences in cfDNAs between patients and controls. Genomic abnormality analysis showed that median PGA score was 9.28 (7.38–11.08) in the 8 controls and 19.50 (5.89–64.47) in the 8 patients ( p = 0.01). Targeted deep sequencing in tumor tissues derived from the 8 patients identified 14 mutations in 12 different genes. The PCR-based assay confirmed 3 of 6 selected mutations in cfDNAs. These results demonstrated that the PGA score and cfDNA mutational analysis could be useful tool for the early detection of lung cancer. These blood-based genomic and genetic assays are noninvasive and may sensitively distinguish early stage disease when combined with other existing screening strategies including low-dose CT scanning.